Peran Penting Tokoh Masyarakat Dalam Pemberantasan Korupsi - Kadek Dedy Suryana (Universitas Mahendradatta, 2019)
The rise of corruption cases revealed lately shows that corruption crime in Indonesia is verymuch a scourge and the heavy duty of the government to eradicate it one by one. Initially corruptionwas still carried out in the form of petty bribes, but now corruption is carried out in the category ofbillions from all aspects, even the last case was revealed to the detention center. It is a tragicphenomenon because our nation is known to have a high cultural morality and a very religiouscommunity. Efforts to eradicate corruption cannot be cut off by what is seen. But must be with broadand deep social movements, leading to social and cultural change. The social movement to eradicatecorruption is a revival of society to jointly correct conditions and bring a better life. The ultimate goalis not only to change the attitudes and behavior of individuals within the community itself, but also tobring about a new social order that is free of corruption. The problem in this journal is how the role ofcommunity leaders becomes very important in the process of eradicating corruption in Indonesia. thecommunity and the encouragement of the community to be aware of corruption must be truly enhanced,including cooperation from the KPK by always providing counseling with community leaders, becausebecause these community leaders are the important spearhead for moving a corruption-awarecommunity system. As a suggestion, the KPK cooperates with community and adat leaders in theformation of rules in the community, for example awig-awig in the Balinese indigenous community.With the awig-awig regulating corruption, it will act as a foundation in the enforcement of anticorruptionitself, which was started at the level of indigenous groups.